Effects of heavy metals (Pb++, Cu++, Cd++, Hg++) on total protein and abscisic acid content of bean (Phaseolus vulgaris L. cv. Strike) seedlings - Zengin, FK; Munzuroglu, O (Parlar Research & Technology Ug, 2006)
The aim of this study was to investigate the levels of total protein and abscisic acid (ABA) of bean plants (Phaseolus vulgaris L. cv. Strike) in the presence of lead, copper, cadmium and mercury. One-week-old seedlings were grown at heavy metal concentrations for ten days in Hoagland's solution. At the end of this period, total protein contents of 17-days old primary leaves were determined by a spectrophotometer, and abscisic acid (ABA) contents in leaves of the seedlinas were measured by high-pressure liquid chromatography. We found that higher heavy metal exposures of the seedlings increased abscisic acid production, which could be related to kind of heavy metal and its concentration (p < 0.05 or p < 0.01). The total protein contents (p < 0.05 or p < 0.01) decreased with heavy metals' concentrations. Thus, heavy metal levels at certain critical points negatively affect seedlings' growth. The heavy metal effect was as follows: mercury > cadmium > copper. Based on this observation, we concluded that any concentration of heavy metal had a bad effect on the growth of seedlings by increasing abscisic acid level and decreasing total protein level.
Keywords: abscisic acid; bean seedling; heavy metal; protein